Isolation and Molecular Identification of Nontuberculous Mycobacterium from Different Species of Fish in Karbala Province, Iraq - Al-Mashhadani, Asmaa A.B.; Al-Gburi, Nagham M. (The Iraqi Journal of Veterinary Medicine, 2020)
This study was designed for isolation and molecular identification of Nontuberculous Mycobacterium (NTM) from fish during the period between October and December 2017 from Karbla province, Iraq. This study included 200 fresh fish samples from four different species including Spondyliosoma cantharus, Liza abu, Carassius carassius and Cyprinuscarpio. Three samples of each fish were taken including gills, muscles and all internal organs. The samples were processed by decontamination, concentration of 4% sodium hydroxide, and 0.1 ml of sediment was streaking on Löwenstein Johnson (LJ) media; then the bacterial cultures were incubated at 28-30 °C for 3days up to 4 weeks and suspected colonies were stained with acid fast stain to confirm the presence of Mycobacterium. Further identification, biochemical tests were carried out to confirm the diagnosis of isolates, PCR was done using 16s RNA gene for all isolates, hsp65 gene was used in unidentified NTM spp and to confirm the others. Results revealed that out of 200 fish samples, 19 isolates 9.5% were identified as NTM belonged to Rapid Growth Mycobacterium (RGM). of the total isolates, 18.26 % was investigated from Liza abu (Kishni, Abu khraiza). NTM (RGM) isolates on spp level identified six spp of these isolates. M. porcinum was 26.32% which was followed by M. fortuitum of 21.05%, others included M. neworleansense and M. mucogenicum 10.5% of each, M. cosmeticum and M. pallens 5.26% of each. The distribution of NTM spp in the fish organs, nine out of 19 (47.37%) NTM isolate were recovered from gills followed by muscles 36.84 %, while 15.79% from internal organs. These results were the first study concerning isolation of these spp of NTM from fish in Iraq, and some spp are not reported in other studies. This study concluded that the fish is an importance source or reservoir for NTM, especially the pathogenic spp.